On some methods of storing data in the cloud for a given time - Banu Yergaliyeva; Yerzhan Seitkulov; Dina Satybaldina; Ruslan Ospanov (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2022)
In this work we study some methods of storing data in the cloud for a given time using secret sharing technology. Such problems are especially relevant in the context of the rapid development of the internet of things (IoT). Chips, smart cards and other physically small devices, as a rule, have significant memory limitations, so there is a need to use cloud storage as an auxiliary tool for secure data storage. We present method for secure storing data in distributed servers, provided that servers remote from each other do not collude with each other. In the paper we also consider two diferent methods for storing data using various cryptographic solutions, such as Shamir's secret sharing method, El Gamal scheme, diffie-hellman key distribution protocol.